RSM optimization of spray-coating parameters to enhance paper strength using cellulose nanocrystals extracted from young coconut husks - Pilaipon Nuthongkum; Russameeruk Noonuruk; Atipong Bootchanont; Porramain Porjai; Chakkaphan Wattanawikkam; Sorapong Pavasupree; Nopparat Tatmala; Nattapong Chanchula; Wisanu Pecharapa; Prasopporn Junlabhut (Nordic Pulp & Paper Research Journal, 2025)
Abstract This study optimizes spray-coating parameters for cellulose nanocrystals extracted from young coconut husks onto paper substrates using response surface methodology. CNCs were produced through acid hydrolysis and mechanical grinding, yielding nanocrystals with an average size of 116 nm and a crystallinity index increase from 28.89 % to 86.13 %. XRD and FTIR analyses confirmed high purity, while UV-vis revealed significant optical absorption in the UV range. Spray-coating parameters, including CNC concentration, volume, heating temperature, and heating duration, were optimized using a central composite design. The 2FI model revealed that CNC concentration and heating duration significantly affected film thickness, where higher CNC levels and longer heating durations produced thicker coatings. However, excessive CNC content led to agglomeration, compromising film quality. The quadratic model highlighted a significant relationship between coating parameters and tensile strength. Heat treatment notably enhanced mechanical properties, with optimal tensile strength reaching 26.15 ± 0.61 MPa-15 % higher than uncoated paper-under conditions of 4 % w/v CNC concentration, 1.5 ml volume, 75 °C heating temperature, and 35 min heating duration. This research highlights the potential of CNCs from young coconut husks as a sustainable reinforcement material, promoting agricultural waste valorization and enhancing paper properties.
Keywords: Advanced Cellulose Research Studies; Nanocomposite Films for Food Packaging; Lignin and Wood Chemistry